Development of Human Brain Sodium Magnetic Resonance Imaging (23Na MRI) Methods - Polak, Paul (My University, 2022)
Sodium (23Na) plays a critical role in all organisms – it is crucial in cellular homeostasis, pH regulation and action potential propagation in muscle and neuronal fibres. Healthy cells have a low intracellular 23Na and high extracellular concentration, with the sodium-potassium pump maintaining this sodium gradient. In the human brain approximately 50% of its total energy consumption is occupied by maintenance of this gradient, demonstrating the pump’s importance in health. A failure of the sodium-potassium pump leads to cellular apoptosis and ultimately necrosis, with potentially disastrous results for neurological function. Magnetic resonance imaging (MRI) of 23Na is of great interest because of the ubiquity of sodium in cellular processes. However, it is hampered by many technical challenges. Among these are a low gyromagnetic ratio, short T2∗ relaxation times, and low concentrations all of which lead to long acquisitions in order to account for the poor inherent signal. In addition, 23Na MRI requires specialized hardware, non-standard pulse sequences and reconstruction methods in order to create images. These have all contributed to render clinical applications for 23Na MRI virtually non-existent, despite research indicating sodium’s role in various neurological disorders, including multiple sclerosis, Alzheimer’s, stroke, cancer, and traumatic brain injury. This work is motivated by a desire to use 23Na MRI in clinical settings. To that end, hardware and software methods were initially developed to process sodium images. In order to quantify the imaging system the point-spread function (PSF) and the related modulation transfer function (MTF) were calculated with the aid of a 3D-printed resolution phantom with different 23Na concentrations in gelatin. Two pulse sequences, density-adapted projection reconstruction (DA-3DPR) and Fermat looped orthogonally encoded trajectories (FLORET), with similar acquisition times were tested. Reconstructions were performed with the non-uniform fast Fourier transform. Results indicated a full-width, half-maximum (FWHM) value of 1.8 for DA-3DPR and 2.3 for FLORET. In a follow-up study, simulation experiments were added to various sodium phantom concentrations in 3% agar. The simulations indicated high potential variability in the MTF calculations depending on the methodology, while the phantom experiments found a FWHMs of 2.0 (DA-3DPR), and 2.5 (FLORET). Diffusion tensor imaging (DTI) is an MRI technique with wide adoption for the assessment of a variety of neurological disorders. Combining DTI with 23Na MRI could provide novel insight into brain pathology; however, a study with a healthy population is warranted before examinations with other populations. Fifteen subjects were scanned with DTI and sodium MRI, and the latter was used to derive voxel-wise tissue sodium concentration (TSC). Regional grey and white matter (WM) TSC was analyzed and compared to fractional anisotropy (FA) and cerebrospinal fluid (CSF) proximity. Results indicated that WM voxels proximal to CSF regions (i.e. corpus callosum) could have lower than expected FA values and higher measured TSC, with an inverse correlation between TSC and distance to CSF. This is likely the result of the broad PSF of 23Na MRI, as regions distal to CSF did not exhibit this phenomenon. This potentially represents a confounding effect when interpreting sodium concentrations, especially in regions proximal to the high 23Na content in CSF.
Keywords: MRI, sodium, point-spread function, brain imaging